Secular trends and factors associated with overweight among Brazilian preschool children: PNSN-1989, PNDS-1996, and 2006/07 - Jonas Augusto C. Silveira; Fernando Antônio B. Colugnati; Monize Cocetti; José Augusto A.C. Taddei (Elsevier, 2014)
Objective: to describe the secular trends in overweight among preschool children in the years 1989, 1996, and 2006, and to identify risk factors associated with this condition in 2006. Methods: anthropometric data from three surveys (1989, 1996, and 2006) with a representative sample of the population were analyzed. Overweight was defined as the weight-for-height Z-score. The multivariable models of overweight association with risk factors were generated by Poisson regression, and the estimates were shown as prevalence ratios with their respective 95% confidence intervals (PR [95% CI]). Results: throughout the 17-year period studied, the relative prevalence of overweight in preschoolers increased by 160% in Brazil, representing an increase of 9.4% per year. Based on data from the National Survey on Demography and Health of Women and Children - 2006/07, four multivariable models were created (macro-environmental, maternal, individual, and final model) assuming hierarchy among the risk factors. In the final model, only the following remained associated with overweight: regions South/Southeast (1.55 [1.17 to 2.06]), middle-class (1.35 [1.02 to 1.77]), maternal obesity (1.66 [1.22 to 2.27]), birth weight ≥ 3.9 kg (1.87 [1.31 to 2.67]), and being an only child or having only one sibling (1.81 [1.31 to 2.49]). Conclusion: the prevalence of overweight among preschool children in Brazil has increased dramatically over the past 17 years, and it was higher in the 1996-2006 period. Future strategies for prevention and control of overweight in public health should focus or intensify actions in communities that are characterized by the presence of the risks identified in the present study. Resumo: Objetivo: descrever a tendência secular do excesso de peso (EP) entre pré-escolares nos anos de 1989, 1996 e 2006 e identificar os fatores de risco associados a esta condição em 2006. Métodos: análise dos dados de três inquéritos antropométricos (1989, 1996 e 2006) com amostra representativa da população brasileira. O EP foi definido como o escore-Z de peso-para-altura > + 2. Os modelos multivariáveis de associação do EP com os fatores de risco foram gerados por meio da regressão de Poisson e as estimativas apresentadas como razão de prevalência com seus respectivos intervalos de confiança de 95% (RP [IC 95%]). Resultados: no período de 17 anos estudado, a prevalência relativa do EP em pré-escolares aumentou em 160% no Brasil, representando incremento de 9,4% ao ano. A partir dos dados da Pesquisa Nacional de Demografia e Saúde da Mulher e da Criança-2006/07 criamos quatro modelos multivariáveis (macroambiental, materno, individual, modelo final) assumindo hierarquia entre os fatores de risco. No modelo final, permaneceram como fatores associados ao EP: as macrorregiões Sul/Sudeste (1,55 [1,17-2,06]), a classe média (1,35 [1,02-1,77]), a obesidade materna (1,66 [1,22-2,27]), o peso ao nascer > 3,9 kg (1,87 [1,31-2,67]) e ser filho único ou possuir um irmão (1,81 [1,31-2,49]). Conclusão: a prevalência de EP entre pré-escolares no Brasil aumentou drasticamente nos últimos 17 anos, sendo mais intenso no intervalo de 1996-2006. Futuras estratégias de prevenção e controle do EP em saúde pública devem considerar em seu escopo, ou intensificar suas ações, nas coletividades que se caracterizem pela presença dos riscos identificados neste trabalho. Keywords: Preschooler, Overweight, Obesity, Epidemiological surveys, Nutritional epidemiology, Brazil, Palavras-chave: Pré-escolar, Sobrepeso, Obesidade, Inquéritos epidemiológicos, Epidemiologia nutricional, Brasil